(untitled) (Eurasian Research Bulletin, 2022)
The teaching of grammar to language learners is the most important aspect of language learning. Word collocation is necessary if fluency must be achieved in the use of the English language. This study focuses on the use of lexical collocation in producing English sentences. Two types of collocation were explained: grammatical collocation and lexical collocation. The attention of this study is focused on lexical collocation. Seven classes of lexical collocation were handled. Various sentence examples were used to show the importance of collocation in grammar. The research concludes that the teaching and learning of collocation of words should be given adequate attention in language classrooms